2005
DOI: 10.1007/s00464-004-8948-0
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary prospective study of the usefulness of a magnetic endoscope locating device during colonoscopy

Abstract: The EPDU was accurate in estimating lesion location. The device also holds promise as an aid in the completion of difficult exams (about 30% of cases in this study).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 18 publications
0
13
0
1
Order By: Relevance
“…The need for accurate preoperative localization of the tumor has triggered the development of different endoscopic techniques to facilitate further tumor identification at the time of surgery, including the use of clips [35] and peritumoral submucosal tattooing [69]. More recently, the use of new technologies such as the “Scope Guide” or “magnetic endoscopic imaging” has been proposed to identify the position of the endoscope in the colon [1012], thereby facilitating lesion location detection. The electromagnetic imaging system has been introduced as an aid to colonoscopy and reveals a great potential for assisting endoscopists without exposing patients or medical staff to radiation.…”
Section: Discussionmentioning
confidence: 99%
“…The need for accurate preoperative localization of the tumor has triggered the development of different endoscopic techniques to facilitate further tumor identification at the time of surgery, including the use of clips [35] and peritumoral submucosal tattooing [69]. More recently, the use of new technologies such as the “Scope Guide” or “magnetic endoscopic imaging” has been proposed to identify the position of the endoscope in the colon [1012], thereby facilitating lesion location detection. The electromagnetic imaging system has been introduced as an aid to colonoscopy and reveals a great potential for assisting endoscopists without exposing patients or medical staff to radiation.…”
Section: Discussionmentioning
confidence: 99%
“…The need of an accurate preoperative localization of the tumor has brought the development of different endoscopic techniques in order to facilitate further tumor identification at the time of surgery, including the use of clips (21)(22)(23) and peritumoral submucosal tattooing (1,22,(24)(25)(26). More recently, the use of new technologies as the "scope guide" or "magnetic endoscopic imaging" has been proposed in order to identify the position of the endoscope in the colon (5,21,27), therefore facilitating detected lesions location. Besides endoscopy, other procedures can help in the localization of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Last but not least, correct localization of pathological findings is very important when surgery is needed or for follow-up examinations. It has been shown that the real-time view of the endoscope is highly accurate in estimating lesion location [11].…”
Section: Discussionmentioning
confidence: 99%
“…Fluoroscopy and magnetic endoscopic imaging systems are able to provide physicians with information regarding scope shape. However, they are limited by cost, cumbersome hardware, and the risk to both patient and staff of ionizing radiation [9][10][11][12][13][14][15][16][17][18]. In this study we evaluated the in vitro mapping capabilities of the NeoGuide Endoscopy System in terms of colonic looping, insertion depth, tip position, and tip angle formation.…”
mentioning
confidence: 99%